A commentary on Book 4 of Valerius Flaccus' Argonautica - Murgatroyd, Paul (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2009)
This commentary examines the text of book 4 of Valerius Flaccus' ""Argonautica, "" and explicates sense and references, but above all, it provides a critical appreciation of the poetry, with a focus on wit, humor, elegance, subtlety, narrative skill and creative engagement with forerunners.